MOTIVASI MAHASISWA KAMPUS 1 UNIVERSITAS NEGERI SURABAYA YANG SERING BERKUNJUNG DI COFFEE SHOP - lailautami laila; Sarmini (Universitas Negeri Surabaya (Unesa), 2026)
Coffee shops are no longer just places to enjoy coffee; they have evolved into multifunctional spaces for students, especially those in major cities like Surabaya. Students at Campus 1 of Surabaya State University are no exception. This phenomenon indicates that coffee shops have a greater appeal than simply providing beverages, but also as part of the student life experience. This study aims to identify and understand the motivations of students who frequently visit coffee shops. The theoretical basis used is the concept of